Effectiveness and cost-effectiveness of universal school-based mindfulness training compared with normal school provision in reducing risk of mental health problems and promoting well-being in adolescence: the MYRIAD cluster randomised controlled trial. Issue 3 (12th July 2022) - Kuyken, Willem; Ball, Susan; Crane, Catherine; Ganguli, Poushali; Jones, Benjamin; Montero-Marin, Jesus; Nuthall, Elizabeth; Raja, Anam; Taylor, Laura; Tudor, Kate; Viner, Russell M; Allwood, Matthew; et al.
Abstract : Background: Systematic reviews suggest school-based mindfulness training (SBMT) shows promise in promoting student mental health. Objective: The My Resilience in Adolescence (MYRIAD) Trial evaluated the effectiveness and cost-effectiveness of SBMT compared with teaching-as-usual (TAU). Methods: MYRIAD was a parallel group, cluster-randomised controlled trial. Eighty-five eligible schools consented and were randomised 1:1 to TAU (43 schools, 4232 students) or SBMT (42 schools, 4144 students), stratified by school size, quality, type, deprivation and region. Schools and students (mean (SD); age range=12.2 (0.6); 11–14 years) were broadly UK population-representative. Forty-three schools (n=3678 pupils; 86.9%) delivering SBMT, and 41 schools (n=3572; 86.2%) delivering TAU, provided primary end-point data. SBMT comprised 10 lessons of psychoeducation and mindfulness practices. TAU comprised standard social-emotional teaching. Participant-level risk for depression, social-emotional-behavioural functioning and well-being at 1 year follow-up were the co-primary outcomes. Secondary and economic outcomes were included. Findings: Analysis of 84 schools (n=8376 participants) found no evidence that SBMT was superior to TAU at 1 year. Standardised mean differences (intervention minus control) were: 0.005 (95% CI −0.05 to 0.06) for risk for depression; 0.02 (−0.02 to 0.07) for social-emotional-behavioural functioning; and 0.02 (−0.03 to 0.07) for well-being. SBMT had a high probability of cost-effectiveness (83%) at a willingness-to-pay threshold of £20 000 per quality-adjusted life year. No intervention-related adverse events were observed. Conclusions: Findings do not support the superiority of SBMT over TAU in promoting mental health in adolescence. Clinical implications: There is need to ask what works, for whom and how, as well as considering key contextual and implementation factors. Trial registration: Current controlled trials ISRCTN86619085 . This research was funded by the Wellcome Trust (WT104908/Z/14/Z and WT107496/Z/15/Z).